New emphasis for SACCAR - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The Southern African Centre for Cooperation in Agricultural Research (SACCAR) Africa's main regional agricultural institution, is to extend its research programme to include work on cash crops. SACCAR was established in 1985 by the Southern African...